Modeling and Quantifying Palm Trees Foliage Loss using LoRa Radio Links for Smart Agriculture Applications - Anzum, Rabeya; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul; Hakim, Galang P. N. (IEEE, 2021)
LoRa LPWAN (Long Range Low Power Wide Area Network) technology is a radio modulation technology which is widely used in various IoT applications for its unique feature of long-range coverage, low power consumption and low deployment and maintenance cost. Because of these features LoRa is mostly chosen for performing communication in agricultural monitoring. In this paper, palm-oil foliage effect has been studied in terms of foliage loss. Specifically, five different sized palm oil trees were studied utilizing 915MHz and 868MHz frequencies to quantify LoRa link loss for three different propagation path crossings the trunk, the canopy, and the treetop. This research was undergone measuring the RSSI data to find the average foliage propagation loss due to a single palm-oil tree. It has been found that the trunk of the palm-oil trees contributes in RSSI degradation while a significant loss is noticed in canopy region of the trees. The result demonstrates the need for further investigations of path loss modelling in Palm-oil plantation environment because the densely scattered leaves and branches of the palm-oil trees will be accountable for significant propagation loss for implementing LoRa-IoT agricultural applications in palm oil plantation.